PENGELOLAAN SAPTA PESONA DI OBJEK WISATA JAM GADANG BUKITTINGGI - Lestari, Tia (journal of residu, 2019)
This study aims to find out the management of charms in the tourist attraction of Bukittinggi Clock Tower. This type of research is descriptive with qualitative data. The informants of this study were the Bukittinggi Tourism Office and managers. The objectives of this study are: (1) Describe hygiene management, (2) Describe Beauty, (3) Describe Hospitality. The sampling technique is purposive sampling. Analysis techniques include: data reduction, data presentation, and conclusion. The results of the study are based on informants' responses, namely: planning related to the objectives to be achieved, namely creating a clean, beautiful and friendly tourist attraction. Organizing consists of manager responsibilities in the form of basic tasks in carrying out operational technical work activities. Direction is carried out by reminding and directing the officer by the tourist manager about the tasks that will be done. Supervision is carried out so that the objectives of tourism objects can be carried out properly and can implement plans that have not been implemented as soon as possible for the sake of cleanliness, beauty and hospitality of tourist attractions so that visitors who come feel comfortable and safe.